Hydrogen Sulfide Plays an Important Role in Diabetic Cardiomyopathy - Zhao, Shizhen; Li, Xiaotian; Li, Xinping; Wei, Xiaoyun; Wang, Honggang (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular diseases is an important complication of diabetes mellitus and the main cause of diabetes death. Diabetic cardiovascular diseases, including diabetic cardiomyopathy and diabetic vascular diseases, are related to many factors, such as hyperglycemia, lipid accumulation, oxidative stress, myocarditis and apoptosis. Hydrogen sulfide (H2S) is a newly discovered signal molecule, which plays an important role in many physiological and pathological processes. Recent studies have shown that H2S is involved in improving diabetic cardiovascular disease, but its mechanism has not been fully elucidated. This review summarizes the researches on the roles and its mechanisms of H2S in diabetic cardiovascular diseases in recent years to provide the basis for the in depth research in the future.